القيمة التشخيصية للدراسة الخلوية (Cytology) في دراسة تضيقات الشجرة الصفراوية - زيزفون, حسان; عيسى, رنا; الخليل, سليمان (Latakia University Journal -Medical Sciences Series, 2017)
أُجري هذا البحث لدراسة دور الدراسة الخلوية (cytology) بالفرشاة في تحديد سبب التضيق ضمن الشجرة الصفراوية . حيث أنّ الفرشاة تُعتبر تقنيةً ذاتَ قيمةٍ كبيرةٍ لتوفير العينات الخلوية أثناء إجراء تصوير الطرق الصفراوية و المعثكلية التنظيري بالطريق الراجع (ERCP) لمرضى التضيق الصفراوي .شملت الدراسة 34 مريضاً مع تضيق صفراوي , و تم إجراء ERCP لجميع المرضى و أخذت عينات للدراسة الخلوية باستخدام الفرشاة . و خلال مدة الدراسة التي بلغت عاماً , تم وضع التشخيص النهائي لجميع هؤلاء المرضى بمقاربة منهجية (سريرية , شعاعية , مخبرية , نسيجية بخزعات جراحية ) . و دُرست حساسية و نوعية الفرشاة لتشخيص التضيق الخبيث و بلغت حساسيتها 57.1% , نوعية 100% , قيمة تنبؤية إيجابية 100% , قيمة تنبؤية سلبية 76.9 % , و دقة تشخيصية 82%.النتيجة : إن الدراسة الخلوية بالفرشاة تملك نوعيةً عاليةً جداً و لكن حساسيةً متوسطة لتشخيص التضيق الخبيث و مع ذلك فيهي ذات فائدةٍ تشخيصيةٍ عاليةٍ للتمييز بين الأسباب الخبيثة و الحميدة للتضيق الصفراوي .This research is designed to study the diagnostic yield of brush cytology for biliary strictures. Brush cytology technique is of a great value to provide cytological samples during ERCP for patients with biliary strictures . The study included 34 patients with biliary stricture, ERCP was performed to all patients and cellular samples were taken using a brush for cytology . During the study period (one year) , the final diagnosis was made using a systematic approach based on clinical, radiological, laboratory or histopathological diagnosis . Sensitivity and specificity of brush cytology were studied . The sensitivity of biliary brushing was 57.1% , specificity was 100%, positive predictive value was 100% , negative predictive value was 76.9% and accuracy was 82% .Conclusions: Brush cytology has a very high specificity but an intermediate sensitivity for the diagnosis of malignant biliary strictures . Despite that , brush cytology is of a high diagnostic utility to distinguish between malignant and benign causes of biliary strictures .